2000
DOI: 10.1023/a:1008332724977
|View full text |Cite
|
Sign up to set email alerts
|

Response and palliation in a phase II trial of gemcitabine in hormone-refractory metastatic prostatic carcinoma

Abstract: Gemcitabine in the dose and schedule indicated above has a significant beneficial impact on pain in patients with hormone-refractory prostatic carcinoma despite its limited activity in terms of PSA response and considerable, especially hematological, toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Its antiproliferative effect in androgenindependent CaP cell lines 31 gave rise to clinical expectations but its benefit in androgen-independent CaP patients was modest mainly due to its peripheral toxicity. [32][33][34] As targeted delivery cannot be based only on a simplified hypothesis that a cancer cell specific ligand will lead to preferable interaction and internalization of the drug in the cancer cell, other important factors should be taken into consideration, such as systemic targeting, tumor penetration, tumor heterogeneity. 43 For this reason, in this manuscript the focus was not only to enrich the repository of GnRH conjugates with new chemical entities which target GnRH-R positive cancer cells, but also to improve the therapeutic potential of gemcitabine, a very potent drug with poor pharmacokinetic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its antiproliferative effect in androgenindependent CaP cell lines 31 gave rise to clinical expectations but its benefit in androgen-independent CaP patients was modest mainly due to its peripheral toxicity. [32][33][34] As targeted delivery cannot be based only on a simplified hypothesis that a cancer cell specific ligand will lead to preferable interaction and internalization of the drug in the cancer cell, other important factors should be taken into consideration, such as systemic targeting, tumor penetration, tumor heterogeneity. 43 For this reason, in this manuscript the focus was not only to enrich the repository of GnRH conjugates with new chemical entities which target GnRH-R positive cancer cells, but also to improve the therapeutic potential of gemcitabine, a very potent drug with poor pharmacokinetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Previous in vitro studies demonstrated that gemcitabine has exceptional antiproliferative effects in androgen-independent CaP cell lines 31 but modest clinical benefit when tested as monotherapy or combination therapy, mainly due to its severe peripheral side effects. [32][33][34] Many efforts aiming to enhance the therapeutic status of gemcitabine by chemical modifications have been reported. 30 These modifications have been focused on either improving gemcitabine's pharmacokinetics or reducing resistance induction.…”
Section: Introductionmentioning
confidence: 99%
“…Hejna et al assessed the regimen Docetaxel, Gemcitabine and granulocyte-colony stimulating factor in treatment of advanced non-small cell lung carcinoma and found this treatment to have significant activity [10]. In the treatment of CRMPC Morant et al showed that single agent gemcitabine had a significant beneficial impact on pain despite its limited efficacy in terms of PSA response [11]. However, there is only limited literature available on the anti-tumour efficacy and tolerance of DGP to treatment of CRMPC.…”
Section: Introductionmentioning
confidence: 99%
“…Starting in 1991, the Swiss Group for Clinical Cancer Research (SAKK) conducted four consecutive phase II trials within the framework of a master protocol to evaluate carboplatin (Jungi et al, 1998), idarubicin (Schmid et al, 1997), gemcitabine (Morant et al, 2000) and vinorelbine (Morant et al, 2002b), in patients with HRPC. The goal of these studies was to find promising new drugs for further testing in phase III trials.…”
mentioning
confidence: 99%